2011
DOI: 10.1016/j.bbamcr.2010.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin-1 processing of ErbB4 in fetal type II cells is necessary for control of fetal lung maturation

Abstract: Maturation of pulmonary fetal type II cells to initiate adequate surfactant production is crucial for postnatal respiratory function. Little is known about specific mechanisms of signal transduction controlling type II cell maturation. The ErbB4 receptor and its ligand neuregulin (NRG) are critical for lung development. ErbB4 is cleaved at the cell membrane by the γ-secretase enzyme complex whose active component is either presenilin-1 (PSEN-1) or presenilin-2. ErbB4 cleavage releases the 80 kDa intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 57 publications
4
34
0
Order By: Relevance
“…Interestingly, there is a genetic correlation between ErbB-4 and schizophrenia (Pan et al 2011) and the involvement of the ICD fragment in controlling gene expression in relevant cell types has been reported (Wong and Weickert 2009;Allison et al 2011). Also, the maturation of fetal lung cells is reported to be dependent on secretase processing of ErbB-4 and ICD association with the transcription factors YAP (Hoeing et al 2011), STAT 5a (Zscheppang et al 2011a), and ERb (Zscheppang et al 2011b). It is suggested that these interactions allow ErbB-4 to regulate transcription of surfactant protein B and thereby promote lung maturation.…”
Section: Secretase Processing Of Rtks Erbb-4 Receptormentioning
confidence: 99%
“…Interestingly, there is a genetic correlation between ErbB-4 and schizophrenia (Pan et al 2011) and the involvement of the ICD fragment in controlling gene expression in relevant cell types has been reported (Wong and Weickert 2009;Allison et al 2011). Also, the maturation of fetal lung cells is reported to be dependent on secretase processing of ErbB-4 and ICD association with the transcription factors YAP (Hoeing et al 2011), STAT 5a (Zscheppang et al 2011a), and ERb (Zscheppang et al 2011b). It is suggested that these interactions allow ErbB-4 to regulate transcription of surfactant protein B and thereby promote lung maturation.…”
Section: Secretase Processing Of Rtks Erbb-4 Receptormentioning
confidence: 99%
“…One potential candidate that is cleaved by TACE is ErbB4. One of the ErbB4 isoforms is subjected to sequential TACE and Presenilin-1 cleavage (7). The released intracellular domain of ErbB4 has been shown to act as a cofactor for Sftpb transcription and type II cell differentiation (12,27).…”
Section: Discussionmentioning
confidence: 99%
“…This phosphorylation activates intracellular signaling pathways such as the phosphatidylinositol-3-kinase/Akt pathway to ultimately influence gene expression (70, 76, 84). Alternatively, ErbB4 may undergo proteolytic processing involving two sequential cleavage processes, first by the transmembrane metalloprotease tumor necrosis factor-α converting enzyme (TACE); and second by the enzyme γ-secretase, a complex of four proteins in which the enzymatic component is either presenilin-1 or presenilin-2 (85, 86). Presenilins are crucial for normal lung development (87).…”
Section: Neuregulin-1βmentioning
confidence: 99%